PENGEMBANGAN PARIWISATA BAHARI (Studi Deskriptif Pada Pelaku Pengembangan Pariwisata Bahari Pantai Watukarung Desa Watukarung Kecamatan Pringkuku Kabupaten Pacitan) - Karina Wulan Sayogi; Argyo Demartoto (Journal of Development and Social Change, 2018)
Abstract :  Tourism has become one of the world's largest industry after oil and gas. Tourism in Indonesia is very complex to be developed into a marine tourism including Watukarung in Pacitan Regency. This research aims to know the marine tourism potential, supporting and restricting factors, strategies, as well as the impact of tourism development on the coast of Watukarung in the village of Watukarng sub-district of Pacitan Regency East Java Pringkuku using a theory of Pierre Bourdieu F Practices. This research is a descriptive qualitative research. The technique of sampling with the purposive sampling. The technique of data collection by observation, interview and documentation. The results of this research show that the tourism potential of the natural potential of the particular form of coastal marine coast Watukarung; social potential that is the attitude of the pillars and royong community; the economic potential that is people's livelihoods as fishermen and tourism businesses in the form of food stalls, homestay, laundry cleaning, and manufacture souvenirs; and potential of culture is karawitan, ketoprak, rontek, and the hadrah.  Keywords: Marine tourism, beach, development, supporting and restricting factors, the impact Abstrak: Pariwisata telah menjadi salah satu industri terbesar di dunia setelah minyak dan gas. Pariwisata di Indonesia sangat kompleks untuk dikembangkan menjadi wisata bahari termasuk Watukarung di Kabupaten Pacitan. Penelitian ini bertujuan untuk mengetahui potensi wisata bahari, faktor pendukung dan pembatas, strategi, serta dampak pengembangan pariwisata di pesisir Watukarung di Desa Watukarang Kecamatan Prapuku Kabupaten Pacitan Jawa Timur menggunakan teori Pierre Bourdieu F Praktik. Penelitian ini merupakan penelitian kualitatif deskriptif. Teknik pengambilan sampel dengan purposive sampling. Teknik pengumpulan data dengan observasi, wawancara dan dokumentasi. Hasil penelitian ini menunjukkan bahwa potensi wisata potensi alam berupa bentuk pantai pesisir laut tertentu Watukarung; potensi sosial yaitu sikap pilar dan komunitas royong; potensi ekonomi yang merupakan mata pencaharian masyarakat sebagai nelayan dan usaha pariwisata dalam bentuk warung makan, homestay, laundry, dan pembuatan souvenir; dan potensi budaya adalah karawitan, ketoprak, rontek, dan hadrah.  Kata kunci: Wisata bahari, pantai, pengembangan, faktor pendukung dan pembatasan, dampaknya